GENETIC VARIATION AND CHARACTER ASSOCIATION STUDY AMONG MORPHOLOGICAL AND BIOCHEMICAL TRAITS OF TOMATO (Solanum lycopersicum L.)GENOTYPES - ANKITA DEBNATH; RAJESH KUMAR; SITA KUMARI PRASAD; NISHA SHARMA (The Bioscan, 2021)
The present investigation was statistically laid out in Randomized Block Design with three replications during 2017-2018 to study genetic variability for yield and quality traits among thirteen tomato (Solanum iycopersicum L.) genotypes. Significant differences were noticed for the twelve quantitative characters and promising genotype ST-102 revealed highest fruit yield per plant (681.32 g) along with maximum ascorbic acid (34.68 mg). Magnitude of phenotypic coefficient of variation was slightly higher than the genotypic coefficient of variation for all the traits. Highest estimate of GCV and PCV was recorded for total phenol content (56.61 % and 56.93 %) respectively. High heritability along with genetic advance as per cent of mean was noticed for total phenol content (99 % and 115.96 %), average fruit weight (91 % and 64.88 %) and fruit yield per plant (90 % and 67.39 %) respectively. Average fruit weight was found to be significantly and positively correlated (0.90 and 0.88) with fruit yield per plant and also produced highest direct effect (0.83 and 0.85) towards fruit yield at both the genotypic and phenotypic levels considering that these traits may be put under selection pressure due to additive gene action towards crop improvement of tomato under organic growing condition.